Anak perempuan dan obesitas sebagai faktor risiko kejadian kadar gula darah tinggi pada anak sekolah dasar - Pibriyanti, Kartika; Hidayati, Khairina Nur (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background : Prevalence of Diabetes Mellitus (DM) in Indonesia is 1.5%. Diabetes Mellitus is not only suffered by adults, but the age of adolescents and children as well. Risk factors in children include gender, obesity, mealtimes, race, age and genetics.Objective : The objective of the study was to analyze the risk factors of high blood glucose incidence in school children.Methods : This research was analytic survey with cross sectional approach. The population was all students of SD Negeri 1 Sokoboyo class IV to VI amounted to 82 students. The sample size was 82 students taken by purposive sampling technique. The independent variables include obesity and sex, as well as the dependent variable that is the blood sugar level. Test analysis used is chi-square test with significance level 5% (Î± = 0,05).Results : Most of the female sample (54.9%), 30.5% were obese and 43.9% had abnormal blood sugar levels. Girls have a 2,95 times greater risk of having high blood sugar levels than boys. Obese children have 10,25 times greater high blood glucose levels than normal children.Conclusion : Sex and obesity are associated with blood sugar levels in students class IV s / d VI SD Negeri 1 Sokoboyo Slogohimo District Wonogiri District.